PENERAPAN TEORI BELAJAR HUMANISTIK MELALUI KURIKULUM MERDEKA DALAM PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Lamberti, Marsela (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research examines how Humanistic Learning Theory is applied in the independent curriculum to create effective IPAS (Natural and Social Sciences) learning in elementary schools because the independent curriculum allows teachers to create more student-oriented learning. The humanistic approach, which emphasizes personal experience, self-actualization, and positive interpersonal relationships, is integrated into IPAS learning to create a positive learning environment, respect students' individuality, and encourage independent exploration. The research was conducted at SDN 010 Barong tongkok with 6 respondents of grade IV students, using a descriptive qualitative approach. The results showed a significant positive impact on learning outcomes and student development. The average LKPD score increased from 60 to 90, with some students even showing remarkable improvements reaching 20 to 42 points, demonstrating the effectiveness of this approach in improving student understanding. The percentage of students achieving KKTP increased from 16.67% to 100%, indicating success in helping students master the subject matter. In addition, observations and interviews revealed an increase in students' active participation, deeper understanding of concepts, and higher motivation to learn. Students also show positive character development such as curiosity, creativity, independence, responsibility, and concern for the environment. These findings confirm that Humanistic Learning Theory, when implemented through the Merdeka Curriculum, can build an empowering learning atmosphere and have a positive impacton students' overall development